(untitled) (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
The evolution of communication technology results in an open, flexible, and heterogeneous wireless network that is more susceptible to malicious attacks. Under such scenarios, massive M2M communication will lead to increase latency and requires more bandwidth. To deal with the network attacks to offer improved QoS is the major challenge in real-time MTC applications. In the paper, a nature-inspired and highly secure mechanism is proposed to authenticate the available respondents based on the fitness function of Artificial Bee Colony (ABC) algorithm and the relationship factor, which is computed in the light of the past performance of the respondents using CRITIC method. The source shares the encrypted data with the respondents that can be decrypted at the terminal based on the key sharing mechanism. The performance of the proposed work mechanism is computed in terms of bandwidth consumption and computation complexity. Simulation analysis against 1000 MTC devices with variable number of intermediate hopes demonstrates that the proposed work exhibits 13% to 14% lesser bandwidth consumption along with 17% lesser computation complexity involved in offering authenticated communication in the LTE network.